Efectos del biofertilizante en los componentes agronómicos y rendimiento de Lactuca sativa L., lechuga, en Zungarococha - Loreto. 2022 - Sanchez Perez, Rai Steven (2023)
The test consisted of determining the effects of biofertilizer on the agronomic components and yield of Lactuca sativa L., lettuce, whose development was in the vegetable lands of Agronomia, on the road to Llanchama, The purpose was to determine the effects of biofertilizer, in the agronomic components and yield of Lactuca sativa L., lettuce, DBCA, It was the applied experimental design, whose treatments were: 0, 10, 20 and 30 t of biofertilizer / ha, where the following conclusions were reached: The biofertilizer, if acted, produced significant effects on Lactuca sativa L., lettuce. The fertilization of 30 t, had in the plant the best height with 29 cm, width of 27 cm, extension of the stem of 20 cm, weight of the stem of 31 g, extension of the root with 6 cm), weight of the root with 4 g, number of leaves / plant (22); in plant with total weight of 131 g, in leaves with weight of 98 g; also, it acquired the highest weight of leaves/ha with 6,533,366 kg and total weight of plant/ha, with 8,733,377. The T3 Treatment with 20 t of biofertilizer, acquired the best economic benefit with S / .10,663.15.